PPengembangan LKPD Trigonometri Berbasis Problem Based Learning Untuk Meningkatkan Kemampuan Berpikir Kreatif Matematika Siswa Kelas X SMK 4 Kota Jambi - Sri Dewi; Relawati Relawati; Risma Simamora (Universitas Batanghari Jambi, 2026)
Creative thinking ability in mathematics is an essential skill that helps students express ideas or concepts to find innovative solutions in problem solving. The purpose of this study is to describe the development process and determine the quality of student worksheets (LKPD) based on Problem Based Learning (PBL) to enhance students’ creative thinking skills in mathematics, assessed through the criteria of validity, practicality, and effectiveness. The research method applied is Research and Development (R&D) using the ADDIE model, with instruments consisting of questionnaires and creative thinking tests. The results show that material validation reached 80% (valid), while design validation reached 95% (very valid). Practicality was rated very practical with percentages of 95.24% by teachers and 88.89% by students. Effectiveness was indicated by student responses of 90.93% (very effective) and the average N-Gain score of 71.23% (effective). Thus, LKPD based on PBL is proven effective in improving students’ creative thinking skills in mathematics.